Covid-19 Lockdown and Changes of Air Quality in the Most Polluted City of Bangladesh - Ferdous, M. N.; Islam, M. A.; Chakrabortty, P.; Kabir, S. (Journal of Scientific Research, 2021)
Air pollution is now a serious issue all over the world. Especially, people of developing countries are seriously affected by air pollution because, like other pollution, air pollution is not given importance. Due to the covid-19 lockdown, pollution is reduced, and as expected, the air quality of Dhaka city has improved. Daily AQI data was collected for the months of April, May and June (2020) and compared with the last six years of data for these months respectively. It was found that the mean AQI of Dhaka city in April, May, and June lower than the last six years in the same period. The mean AQI decreased 43.52 %, 22.37 %, 9,82 %, 16.38 %, 41.43 %, 34.16 % in April when compared with April 2014-2019 respectively and the mean AQI decreased 33.69 %, 37.97 %, 39.25 %, 36.81 %, 45.59 %, 44.15 % in May when compared with May 2014-2019 respectively. The mean AQI decreased 26.48 %, 11.40 %, 8.28 %, 30.61 %, 36.37 % and increase 3.07 % in June (2020) when it compared with June 2014-2019 respectively. This study includes the statistical examination of air quality before and at the time of covid-19 lockdown in Dhaka city.